Untargeted metabolomics reveals predominant alterations in primary metabolites of broccoli sprouts in response to pre-harvest selenium treatment. (September 2018) - Tian, Ming; Xu, Xiaoyun; Liu, Fengxia; Fan, Xin; Pan, Siyi
Abstract: Broccoli sprouts have attracted considerable attention because of their abundant phytochemicals and high selenium accumulation capacity, which reportedly reduce the risks of different cancers and cardiovascular diseases. In this study, an untargeted metabolomics approach was developed to investigate the effect of 5 days of treatment with 100 μmol/L selenate on the metabolome of broccoli sprouts. Results showed that the total sulfur content was slightly lower and the total selenium content was significantly higher in the selenate-treated sprouts. The multivariate statistical analyses showed that serine, d -erythronolactone, melezitose and tyrosine were obviously up-regulated, but d -glyceric acid, succinic acid and citric acid were down-regulated after selenate treatment. Moreover, metabolite pathway analyses were used to support the identification of subtle but significant changes among groups of related metabolites that cannot be observed with conventional approaches. Selenate treatment influenced the metabolism of β-alanine and glutathione, as well as the biosynthesis of plant metabolite related to the precursors of glucosinolate. These results could explain why the total glucosinolate decreased after selenate treatment. Graphical abstract: Unlabelled Image Highlights: Effects of Se treatment on GSL metabolism was treated by 100 μmol/L selenate. The selenate treatment influence the total S content slightly. Parts of primary metabolites were significantly influenced such as serine, D-erythronolactone. Selenate treatment mainly influenced the metabolism of β-alanine and glutathione.